Analyse the Role of Family in Entrepreneurship Education: Effective Support and Assistance - Muhammad Ade Kurnia Harahap; Abu Muna Almaududi Ausat; Sutrisno Sutrisno; Suherlan Suherlan; Hizbul Khootimah Azzaakiyyah (Journal on Education, 2023)
Entrepreneurship education is considered important in developing entrepreneurial skills and preparing individuals to start their own business. One of the factors that influence an individual's ability to start a business is the family's role in supporting entrepreneurship education. This research aims to discuss the role of family in supporting entrepreneurship education and provide useful information for individuals, families, and educational institutions in improving entrepreneurship education. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display and conclusion drawing. The study concluded that the family plays a very important role in developing entrepreneurship, especially in providing the support and learning needed for individuals who want to start a business. The role of family also helps strengthen the development of social and managerial skills in entrepreneurship.